Between Soul and Spirit: Rohr’s Transformational Spirituality in Pastoral Work - Červenková, Denisa (Communio viatorum, 2023)
In this paper some typical features of the spirituality of Richard Rohr, one of popular authors who represents one of the dis-tinctive currents of contemporary Catholic spirituality, are described. I focus on several distinctive characteristics that we find captured in his spiritual texts. These include an emphasis on orthopraxy, on the trans-formative nature of spirituality, on contemplation, and on the embod-ied nature of spirituality. Understanding these basic characteristics, also helps to understand the more general tendency of contemporary spirituality, especially that which consciously straddles the boundary between traditional religious offerings and non-traditional forms of spirituality in non-religious settings.